Propuesta de diseño de un sistema anaerobio tipo biodigestor, para el tratamiento de estiércol bovino generado en el establo, en la sede Usme de la Universidad Antonio Nariño. (2024)
To carry out an optimal management and proper administration of bovine wastewater generated in the stable area of the Usme campus of the Antonio Nariño University was a challenge and pending obligation that the institution had regarding the issue of wastewater discharges without prior treatment. In this research project, a focus is placed on the design proposal for a wastewater treatment system (STAR), to solve the problem presented. Through a methodology focused on 4 main axes; the recognition of the study area, the prefeasibility evaluation of the proposed project, the complete design of the chosen treatment system which is a continuous flow tubular biodigester and the financial analysis of the total investment necessary to develop the proposal set out in the research project.